Risk factors for post-traumatic stress disorder among UK Armed Forces personnel. - Iversen, A; Fear, N; Ehlers, A; Hacker Hughes, J; Hull, L; Earnshaw, M; Greenberg, N; Rona, R; Wessely, S; Hotopf, M (2008)
BACKGROUND: There is considerable interest in understanding further the factors that increase the risk of post-traumatic stress disorder (PTSD) for military personnel. This study aimed to investigate the relative contribution of demographic variables; childhood adversity; the nature of exposure to traumatic events during deployment; appraisal of these experiences; and home-coming experiences in relation to the prevalence of PTSD 'caseness' as measured by a score of 50 on the PTSD Checklist (PCL) in UK Armed Forces personnel who have been deployed in Iraq since 2003. METHOD: Data were drawn from the first stage of a retrospective cohort study comparing UK military personnel who were deployed to the 2003 Iraq War with personnel serving in the UK Armed Forces on 31 March 2003 but who were not deployed to the initial phase of war fighting. Participants were randomly selected and invited to participate. The response rate was 61%. We have limited these analyses to 4762 regular service individuals who responded to the survey and who have been deployed in Iraq since 2003. RESULTS: Post-traumatic stress symptoms were associated with lower rank, being unmarried, having low educational attainment and a history of childhood adversity. Exposure to potentially traumatizing events, in particular being deployed to a 'forward' area in close contact with the enemy, was associated with post-traumatic stress symptoms. Appraisals of the experience as involving threat to one's own life and a perception that work in theatre was above an individual's trade and experience were strongly associated with post-traumatic stress symptoms. Low morale and poor social support within the unit and non-receipt of a home-coming brief (psycho-education) were associated with greater risk of post-traumatic stress symptoms. CONCLUSIONS: Personal appraisal of threat to life during the trauma emerged as the most important predictor of post-traumatic stress symptoms. These results also raise the possibility that there are important modifiable occupational factors such as unit morale, leadership, preparing combatants for their role in theatre which may influence an individual's risk of post-traumatic stress symptoms. Therefore interventions focused on systematic preparation of personnel for the extreme stress of combat may help to lessen the psychological impact of deployment.